A CFD Based Sonic Boom Prediction Method and Investigation on the Parameters Affecting the Sonic Boom Signature. (2015) - Lengyan,; Zhansen, Qian
Abstract: Based on bodies of revolution, several flight and shape parameters are considered for investigating their effects on the sonic boom signature including overpressure and impulse. Here, the parameters include flight altitude, Mach number, cone half-angle, bluntness and fineness ratio. Mach numbers are varied from 1.41 to 4.63 due to publicized wind tunnel experimental data for reference. Near-field domain at the flight altitude is modeled by the conservative Euler equations, and the far-field region computations are carried out using the Thomas ray tracing method. According to the parametric analysis, it is found that sonic boom can be reduced by increasing flight altitude, decreasing cone half-angle, increasing fineness ratio or decreasing Mach number. However, with the increase of bluntness parameter, the overpressure on the ground decreases first and then rises, and the sonic boom impulse shows the similar trend as the overpressure when the Mach number is between 2.96 and 4.63, but for Mach number of 1.41 to 2.01, the impulse increases near linearly with the increasing of the bluntness parameter.